A High-Yielding Rice Cultivar “Takanari” Shows No N Constraints on CO2 Fertilization - Hasegawa, Toshihiro; Sakai, Hidemitsu; Tokida, Takeshi; Usui, Yasuhiro; Nakamura, Hirofumi; Wakatsuki, Hitomi; Chen, Charles P.; Ikawa, Hiroki; Zhang, Guoyou; Nakano, Hiroshi; Matsushima, Miwa Yashima; Hayashi, Kentaro (Frontiers in Plant Science, 2019)
Enhancing crop yield response to elevated CO2 concentrations (E-[CO2]) is an important adaptation measure to climate change. A high-yielding indica rice cultivar ‘Takanari’ has recently been identified as a potential candidate for high productivity in E-[CO2] resulting fromowing to its large sink and source capacities. To fully utilize these traits, nitrogen should play a major role, but it is unknown how N levels influence the yield response of Takanari to E-[CO2]. We therefore compared grain yield and quality of Takanari with those of Koshihikari, a standard japonica cultivar, in response to Free-Air CO2 enrichment (FACE, +200 μmol mol-1) under three N levels (0, 8, and 12 g m-2) over three seasons. The biomass of both cultivars increased under E-[CO2] at all N levels; however, the harvest index decreased under E-[CO2] in the N- limited treatment for Koshihikari but not for Takanari. The decreased harvest index of Koshihikari resulted from limited enhancement of spikelet number under N- limitation. In contrast, spikelet number increased in E-[CO2] in Takanari even without N application, resulting in significant yield enhancement, averaging 18% over 3 years, whereas Koshihikari exhibited virtually no increase in yield in E-[CO2] under the N- limited condition. Grain appearance quality of Koshihikari was severely reduced by E-[CO2], most notably in N- limited and hot conditions, by a substantial increase in chalky grain, but chalky grain % did not increase in E-[CO2] even without N fertilizer. These results indicated that Takanari could retain its high yield advantage over Koshihikari with limited increase in chalkiness even under limited N conditions and that it could be a useful genetic resource for improving N use efficiency under E-[CO2].